(untitled) (Zoological Records and Reviews, 2025)
Animal responses to climate variability – encompassing both long-term directional change and short-term inter-annual and seasonal fluctuations – span a hierarchy of biological organisation from molecular and physiological adjustments within individuals, through phenological and behavioural plasticity, to population demographic responses, distributional shifts, and ultimately evolutionary adaptation or local extinction. Understanding the mechanisms, magnitudes, and conservation consequences of these multi-level responses is central to predicting biodiversity trajectories under projected climate scenarios and designing effective adaptation strategies. This review synthesises evidence from 228 primary studies (2005-2025) examining animal responses to climate variability across European terrestrial, freshwater, and marine ecosystems, evaluating six response domains: phenological shifts, distributional range changes, demographic rate changes, physiological stress responses, evolutionary adaptation, and multi-species interaction disruptions (phenological mismatches). European breeding bird arrival dates have advanced by a mean 5.8 +- 1.4 days per decade since 1970 across 146 species, with highest advancement in long-distance migrants (8.4 days/decade) and lowest in short-distance migrants (3.2 days/decade). Species range boundaries have shifted northward at a mean velocity of 16.4 +- 4.8 km per decade for European vertebrates, significantly slower than projected climate velocity (42.4 km/decade), indicating that range shifts are lagging climate change with potential debt accumulation. Phenological mismatches between consumers and their peak prey availability show non-linear relationships with climate anomaly magnitude, with mismatches exceeding 14 days associated with significant declines in reproductive success. Synthesis identifies trait-based vulnerability predictors and a hierarchical adaptation management framework for European vertebrate conservation under projected 2050 and 2100 climate scenarios aligned with EU Habitats Directive Article 17 reporting needs.